Functional characterization of five NR5A1 gene mutations found in patients with 46, XY disorders of sex development. Issue 1 (8th November 2017) - Fabbri‐Scallet, Helena; de Mello, Maricilda Palandi; Guerra‐Júnior, Gil; Maciel‐Guerra, Andréa Trevas; de Andrade, Juliana Gabriel Ribeiro; de Queiroz, Camila Maia Costa; Monlleó, Isabella Lopes; Struve, Dagmar; Hiort, Olaf; Werner, Ralf
Abstract: Steroidogenic factor‐1 (SF1), encoded by the NR5A1 gene, is a key regulator of steroidogenesis and reproductive development. NR5A1 mutations described in 46, XY patients with disorders of sex development (DSD) can be associated with a range of conditions of phenotypes; however, the genotype–phenotype correlation remains elusive in many cases. In the present study, we describe the impact of five NR5A1 variants (three novel: p.Arg39Cys, p.Ser32Asn, and p.Lys396Argfs*34; and two previously described: p.Cys65Tyr and p.Cys247*) on protein function, identified in seven patients with 46, XY DSD. In vitro functional analyses demonstrate that NR5A1 mutations impair protein functions and result in the DSD phenotype observed in our patients. Missense mutations in the DNA binding domain and the frameshift mutation p.Lys396Argfs*34 lead to both, markedly affected transactivation assays, and loss of DNA binding, whereas the mutation p.Cys247* retained partial transactivation capacity and the ability to bind a consensus SF1 responsive element. SF1 acts in a dose‐dependent manner and regulates a cascade of genes involved in the sex determination and steroidogenesis, but in most cases reported so far, still lead to a sufficient adrenal steroidogenesis and function, just like in our cases, in which heterozygous mutations are associated to 46, XY DSD with intact adrenal steroid biosynthesis. Abstract : We describe the impact of five NR5A1 mutations (p.Arg39Cys, p.Ser32Asn, p.Cys65Tyr, p.Cys247* and p.Lys396Argfs*34) to protein function, identified in seven patients with 46, XY DSD. In vitro functional analyses demonstrate that NR5A1 mutations impair protein functions and result in the DSD phenotype observed in our patients.